Perancangan Basis Data Kawasan Suci Danau Tamblingan dengan Menerapkan Model Data Relasional - I Made Sugi Ardana; Yan Mitha Djaksana (Jurnal Syntax Admiration, 2023)
The indigenous community of Tamblingan highly reveres the forest as the true source of life (Merta Jati). Within the forest area, there are temples and shrines that are interconnected. Information about these sacred temples and shrines is currently limited to a few individuals who possess specific manuscripts, making it not easily accessible. A database is a crucial component of information technology implementation, as it facilitates faster information retrieval, enhances data security, and reduces data storage redundancy. The Database Lifecycle (DBLC) is a method that outlines the life cycle of a database. In this study, the design of a database for the sacred area of Lake Tamblingan is carried out, starting from conceptual database design to physical database design using a relational model. The design is created using the Power Designer tool. Data collection is conducted through literature review and interviews, while data processing is performed through descriptive analysis. This research aims to produce a database design for the sacred area of Lake Tamblingan that can be utilized for further studies, such as developing an information system for the sacred area of Lake Tamblingan.